Morphological control for high performance, solution-processed planar heterojunction perovskite solar cells - Eperon, G; Burlakov, V; Docampo, P; Goriely, A; Snaith, H (Wiley, 2013)
Organometal trihalide perovskite based solar cells have exhibited the highest efficiencies to-date when incorporated into mesostructured composites. However, thin solid films of a perovskite absorber should be capable of operating at the highest efficiency in a simple planar heterojunction configuration. Here, it is shown that film morphology is a critical issue in planar heterojunction CH3NH3PbI3-xCl x solar cells. The morphology is carefully controlled by varying processing conditions, and it is demonstrated that the highest photocurrents are attainable only with the highest perovskite surface coverages. With optimized solution based film formation, power conversion efficiencies of up to 11.4% are achieved, the first report of efficiencies above 10% in fully thin-film solution processed perovskite solar cells with no mesoporous layer. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.